IMPROVING STUDENTS’ READING COMPREHENSION BY USING GUESSING MEANING FROM CONTEXT - Etty Pratiwi; Dewi Kartikasari (Universitas PGRI Palembang, 2020)
The researchers had found that learning reading are (1) investigating whether there was a significant difference of students’ reading comprehension achievement before and after being taught by using Guessing Meaning from Context strategy, (2) findingout in terms of strategies for Guessing Meaning from Context which strategies produced better achievement by the students.The researchers carried out quantitative study with one group Pre-test Post-test Design, involving one class as experimental class. The instrument in this research was reading test. The data analysis showed there was a significant difference on students’ reading comprehension achievement after being taught by using Guessing Meaning from Context strategy. Then, surrounding words, pictures, experience, and imagination as the strategiesincreased the most than the otherstrategies. Hypothesis test showed that the significance value (2- tailed) was 0.000 (p<0.05). It could be concluded that null-hypothesis was rejected. So, the result of the research inferred Guessing Meaning from Context to be able to improve the students’ reading comprehension in all aspects. Keywords: guessing meaning from context, improving, reading skill.